Genetic diversity of Potato virus M (PVM) in the major potato growing region in the Indo-Gangetic plain and characterization of a distinct strain of PVM occurring in India - Kumar, Alok; Katiyar, Akshay; Jailani, A. Abdul Kader; Chackraborty, Ashis; Mandal, Bikash (Frontiers in Microbiology, 2023)
Potato virus M (PVM) is one of the most prevalent viruses infecting potatoes worldwide showing wide range of diversity in their populations, however the diversity and genome information of PVM occurring in India is hardly known. The present study serologically detected the PVM in 22.8% of leaf samples collected from the potato fields, generated 13 coat protein (CP) gene and one complete genome sequences for the isolates from India, and identified four differential hosts confirming PVM-Del-144 as a distinct strain of PVM occurring in India. The phylogenetic analyses conducted based on the CP gene sequences (14 from India and 176 from other countries) suggested the existence of three evolutionary divergent lineages (PVM-o, PVMd and a new divergent group) in PVM population, where isolates from India belongs to only two clusters (PVM-o, and PVM-d) within four sub-clusters. High level of nucleotide diversity (0.124) and genetic distance (0.142) recorded among the isolates from India, may be due to the deviation from the neutral evolution and experiencing population expansion in past. The complete genome of the isolate Del-144 (KJ194171; 8526 nucleotides) shared 92.2-93.9% nt sequence identity with the population of PVM-o, whereas it shared only 70.2-72.1% identity with PVM-d. In the phylogenetic analyses, Del-144 clustered with the isolates of PVM-o, however it formed separate branch away from all other isolates, indicating diversity of the strain.2Overall, this study revealing the diversity of the isolates of PVM from India and reporting the first complete genome sequence of a distinct strain of PVM occuring in India.